Implementation Project for Strengthening the Profile of Pancasila Students (P5) with the Theme of Local Wisdom at SDN 1 Kondangsari - Nugraha, Fivo; Kause, Migdes Christianto; Tafuy, Ardi Y. (Program Studi Tadris IPS Fakultas tarbiyah IAIN Kudus, 2023)
The Independent Curriculum can be interpreted through the implementation of independent learning-based learning in elementary schools as a project to strengthen the profile of Pancasila (P5) students. This curriculum adjustment is a form of the government's seriousness in dealing with problems that occur in the world of education. One of the problems currently occurring is the fading of cultural values based on local wisdom in students' identities. Students tend to be interested in gadgets and foreign culture that is gained from using these gadgets. In this way, the author wants to discuss the implementation of strengthening the cultural values listed in lesson P5 with the P5 theme discussed being local wisdom in phase C of elementary school. This research was carried out in class 5b at SDN 1 Kondangsari. The aim of this research is to determine the application of P5 learning and its impacts. The method used is qualitative with a descriptive approach. Data was collected using interview and documentation techniques. The samples taken were 30 grade 5 elementary school students. The result of this research is that the implementation of p5 with the theme of local wisdom at SDN 1 Kondangsari has been running quite uniquely and creatively. This can be seen from the outdoor- based learning process which is fun and blends with nature.